A Correlation Between The Role of Health Workers and Ytratment Supervisors (PMO) with Medication Adherence of Pulmonary TB Patients in Coastal Area of Tanjung Kemuning Health Cenrer in Kaur Regency - Seventri Herma Handayani; Yusran Fauzi; Wulandari Wulandari (Universitas Dehasen Bengkulu, 2026)
Background: Mycobacterium tuberculosis is the TB germ that causes tuberculosis (TB) in humans. Although it can affect other organs, TB mostly attacks the lungs. According to the Health Office Profile of Kaur Regency, in 2022, there were 103 cases of pulmonary TB. In 2023, there were 121 cases, and in 2024, there were 106 cases. (the Health Office Profile of Kaur Regency, 2024).Objective: This study aims to determine the correlation between the roles of health workers and medication supervisors with adherence to pulmonary TB medication.Methods: The study used a cross-sectional design. The population in this study was all pulmonary TB patients in Kaur Regency, with a total of 38 patients. The sample was drawn using total sampling. The results are presented in univariate and bivariate analyses using the chi-square test at 5% α.: Research results: The results showed a significant relationship between the role of health workers and medication adherence in the coastal area of ​​the Tanjung Kemuning Health Center in Kaur Regency (p=0.011). There was a significant correlation between the role of medication supervisors and medication adherence in the coastal area of ​​the Tanjung Kemuning Health Center in Kaur Regency (p=0.022). Conclusion : It is recommended that the results of this study provide additional data for the community health center in evaluating improvements to infectious disease programs, particularly for pulmonary tuberculosis.